Parallel blade-vortex interaction on pitching airfoil - Colli, A.; Gilbertini, G.; Krishna, P.U.; Marchesi, V.; Zanotti, A. (My University, 2021)
A wind tunnel test campaign was conducted to study the effects of parallel blade-vortex interaction on a retreating rotor blade, in particular in relation to the possible triggering of stall. A tandem configuration was succesfully used, with an upstream airfoil model which was impulsively pitched to generate a vortex, that subsequently interacted with a downstream NACA 23012 airfoil, representing the blade. Different conditions of angle of attack of the blade and relative trajectory of the vortex were studied. PIV measurements were taken to characterise the vortex and to investigate the flow on the suction side of the blade model during the BVI. The results show an effect of the vortex approach on a separated flow region in the case of high angle of attack of the blade. Preliminary test with the blade model oscillating have been performed, to simulate the pitching motion experienced by an actual rotor blade.